Combining branched copolymers with additives generates stable thermoresponsive emulsions with in situ gelation upon exposure to body temperature - Rajbanshi, A; Mahmoudi, N; Murnane, D; Pavlova, E; Slouf, M; Dreiss, C A; Cook, M T (International journal of pharmaceutics, 2023)
Branched copolymer surfactants (BCS) containing thermoresponsive polymer components, hydrophilic components, and hydrophobic termini allow the formation of emulsions which switch from liquid at room temperature to a gel state upon heating. These materials have great potential as in situ gel-forming dosage forms for administration to external and internal body sites, where the emulsion system also allows effective solubilisation of a range of drugs with different chemistries. These systems have been reported previously, however there are many challenges to translation into pharmaceutical excipients. To transition towards this application, this manuscript describes the evaluation of a range of pharmaceutically-relevant oils in the BCS system as well as evaluation of surfactants and polymeric/oligomeric additives to enhance stability. Key endpoints for this study are macroscopic stability of the emulsions and rheological response to temperature. The effect of an optimal additive (methylcellulose) on the nanoscale processes occurring in the BCS-stabilised emulsions is probed by small-angle neutron scattering (SANS) to better comprehend the system. Overall, the study reports an optimal BCS/methylcellulose system exhibiting sol-gel transition at a physiologically-relevant temperature without macroscopic evidence of instability as an in situ gelling dosage form.
Keywords: Thermogelling; Hydrogels; polymery; methylcelulosa; teplota; tělesná teplota; emulze; Stimuli-responsive; Neutron scattering; Polymers; Temperature-responsive; povrchově aktivní látky; Temperature; Surface-Active Agents; Methylcellulose; Body Temperature; hydrogely; Emulsions